Calcium-triggered acrosomal exocytosis in human spermatozoa requires the coordinated activation of Rab3A and N-ethylmaleimide-sensitive factor - Michaut, M. (The National Academy of Sciences, 2000)
The acrosome reaction of spermatozoa is a complex, calcium-dependent, regulated exocytosis. Fusion at multiple sites between the outer acrosomal membrane and the cell membrane causes the release of the acrosomal contents and the loss of the membranes surrounding the acrosome. However, very little is known about the molecules that mediate and regulate this unique fusion process. Here, we show that N-ethylmaleimide-sensitive factor (NSF), a protein essential for most fusion events, is present in the acrosome of several mammalian spermatozoa. Moreover, we demonstrate that calcium-dependent exocytosis of permeabilized sperm requires active NSF. Previously, we have shown that the addition of the active (GTP-bound) form of the small GTPase Rab3A triggers exocytosis in permeabilized spermatozoa. In the present report we show that Rab3A is necessary for calcium-dependent exocytosis. The activation of Rab3A protects NSF from N-ethylmaleimide inhibition and precludes the exchange of the endogenous protein with recombinant dominant negative mutants of NSF. Furthermore, Rab3A activation of acrosomal exocytosis requires active NSF. Our results suggest that, upon calcium stimulation, Rab3A switches to its active GTP-bound form, triggering the formation of a protein complex in which NSF is protected. This process is suggested to be an essential part of the molecular mechanism of membrane fusion leading to the release of the acrosomal contents.